ORGANISATION OF KEDAH TUA FESTIVAL WELLRECEIVED, GAINED RECOGNITION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
SUNGAI PETANI, 23 May 2016 – The organisation of the Kedah Tua Festival (FKT) 2016 for 3 days at the Sungai Batu Archaeological Site has made an impact in featuring the early Kedah Tua civilisation and establishing it as an icon on the world map.